Differential gene expression analysis of Paracoccidioides brasiliensis during keratinocyte infection - Silva, Roberta Peres da [UNESP]; Matsumoto, Marcelo Teruyuki [UNESP]; Braz, Jaqueline Derissi [UNESP]; Voltan, Aline Raquel [UNESP]; de Oliveira, Haroldo Cesar [UNESP]; Soares, Christiane Pienna [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Soc General Microbiology, 2011)
Paracoccidioides brasiliensis is the agent of paracoccidioidomycosis, one of the most important systemic fungal diseases in Latin America. This initiates in lung tissue and can subsequently disseminate to other tissues. Clinical manifestations range from localized forms to disseminated disease that can progress to lethality, probably depending on the relationships among the virulence of the fungus, the immune response and the ability to interact with the surface structures and invade epithelial cells and mononuclear cells of the host. It is generally regarded as a multifocal disease, with oral lesions as the prominent feature. The aim of this study was to evaluate P. brasiliensis yeast infection in normal oral keratinocytes (NOKs). The differential expression of mRNAs and proteins was also determined when the fungus was placed in contact with the cell in order to characterize differentially expressed genes and proteins during P. brasiliensis infection. After contact with NOKs, the fungus appeared to induce alterations in the cells, which showed cellular extensions and cavitations, probably resulting from changes in the actin cytoskeleton seen at 5 and 8 h after infection. Levels of protein expression were higher after reisolation of the fungus from infected NOK culture compared with culture of the fungus in medium. The analysis identified transcripts related to 19 proteins involved in different biological processes. Transcripts were found with multiple functions including induction of cytokines, protein metabolism, alternative carbon metabolism, zinc transport and the stress response during contact with NOKs. The proteins found suggested that the yeast was in a stress situation, as indicated by the presence of RDS1. Nevertheless, the yeast seemed to be proliferating and metabolically active, as shown by the presence of a proteasome, short-chain acetylator, glucosamine-6-phosphate isomerase and ADP/ATP carrier transcripts. Additionally, metabolic pathways may have been activated in order to eliminate toxic substances from the cell as a zinc transporter was detected, which is a potential target for the development of future drugs.